Online Leave Information System Based On Website Case Study At Taman Mini Indonesia Indah - Herman Kuswanto; Agus Mukti Sukarno; Muhamad Ryansyah (Jurnal Mantik, 2020)
Along with the era development and the increasingly advanced technology, demanded speed and accuracy in obtaining information. The use of computers and Sistem-sistemnya has become a major necessity to facilitate human work. Taman Mini Indonesia Indah is an Indonesian culture-themed tourist park in East Jakarta. Leave is one of the employees ' rights. Leave can be used by employees to not be able to enter the work for a particular reason, e.g. refreshing, sick break, childbirth, performing religious obligations, and other purposes in accordance with the provisions of the leave of each organization/agency. Processing of leave data at Taman Mini Indonesia Indah is still done manually by using the leave paper to HRD which resulted in the approval process and the report has not been efficient. With the online website-based and make with method waterfall leave submission system, make it easier for employees to apply for leave and generate fast, precise and accurate data for HRD in obtaining and making employee leave reports.